The Freemasons, the Revolution and socio-political action in the 1930s and 1940s in Pernambuco - Acioly Paz Silva, Augusto César (2018)
This article is a reflection on the role played by Pernambuco Masons, upon the 1930 Revolution discussing their strategies, institutions, while detailing how they forwarded the movement by the foundation of lodges and libraries thus fostering public debate. and strenghtening their positions in the political and intellectual scene in Pernambuco, Brazil, in the 1930’s and 40’s and its connections with the rest of Brazil and the world.